Parallels in Sepsis and COVID-19 Conditions: Implications for Managing Severe COVID-19 - Olwal, Charles Ochieng’; Nganyewo, Nora Nghuchuzie; Tapela, Kesego; Djomkam Zune, Alexandra Lindsey; Owoicho, Oloche; Bediako, Yaw; Duodu, Samuel (Frontiers in Immunology, 2021)
Sepsis is a life-threatening systemic illness attributed to a dysregulated host response to infection. Sepsis is a global burden killing 11 million persons annually. In December 2019, a novel pneumonia condition termed coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged, and has resulted in more than 1,535,982 deaths globally as of 8th December 2020. These two conditions share many pathophysiological and clinical features. Notably, both sepsis and COVID-19 patients experience consumptive thrombocytopenia, haemolytic anaemia, vascular microthrombosis, multi-organ dysfunction syndrome, coagulopathy, septic shock, respiratory failure, fever, leukopenia, hypotension, leukocytosis, high cytokine production and high predisposition to opportunistic infections. Considering the parallels in the pathogenesis and pathophysiological manifestations of sepsis and COVID-19, it is highly likely that sepsis care, which has a well-established history in most health systems, could inform on COVID-19 management. In view of this, the present perspective compares the immunopathogenesis and pathophysiology of COVID-19 and non-SARS-CoV-2 induced sepsis, and lessons from sepsis that can be applicable to COVID-19 management.